Molecular epidemiology of Theileria annulata infection of cattle in Layyah District, Pakistan - Parveen, Asia; Ashraf, Sehrish; Aktas, Munir; Ozubek, Sezayi; Iqbal, Furhan (Springer, 2021)
Theileria annulata is the cause of tropical theileriosis in cattle in Pakistan, where it has a significant impact on the cattle industry. Here we report the molecular detection and seasonal prevalence and blood parameters of T. annulata infection in crossbred, Holstein Frisian and Sahiwal breed in Layyah District in the Punjab. In total, 844 blood samples (cross = 244, Holstein Frisian = 300, Sahiwal breed = 300) collected in 2017 and 2018 were tested. Blood smear screening revealed 125/844 (15%) of cattle positive for Theileria species. PCR amplification of cytochrome b gene indicated an overall T. annulata prevalence of 21% (174/844). The highest prevalence was observed in autumn season (53%), followed by winter (20%), summer (14%) and spring (3%). Crossbred cattle were the most susceptible to T. annulata (28%) followed by Sahiwal (19%) and Holstein Frisian. Representative partial cytochrome b gene sequences of T. annulata revealed phylogenetic similarities with sequences submitted from India, Iran, China, Turkey and Spain. Small numbers of ticks, including Hyalomma anatolicum, Hyalomma excavatum, Rhipicephalus microplus, and Haemaphysalis punctata, were identified from cattle but none of them was found PCR positive for the presence of T. annulata. Analysis of the hematology data indicated that red blood cell, hemoglobin, mean cell hemoglobin, mean corpuscular hemoglobin, lymphocyte (%), monocyte (%) and platelet count were significantly altered in T. annulata-positive cattle of all three breeds. Screening of cattle by PCR for the detection of T. annulata is recommended for diagnosis and treatment.
Keywords: Cytochrome b gene; PCR; Theileria annulate; Phylogenetic analysis; Cattle